2020
DOI: 10.1002/pd.5774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spontaneous fetal loss rates between women with singleton and twin pregnancies after mid‐trimester amniocentesis ‐ A historical cohort study

Abstract: Objective To assess and compare fetal loss rates before 28 weeks of singleton and twin pregnancies after mid‐trimester amniocentesis. Method This historic cohort study included 13 773 women with singletons and 426 women with twins undergoing mid‐trimester amniocentesis from 1/2015 to 3/2017. Pregnancies resulting in termination or selective reduction before 28 weeks were excluded, as well as twin gestations undergoing single‐puncture amniocentesis. Fetal loss rates were compared between singleton and twins tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Only abnormal ultrasound findings were associated with increased risk, similar to that reported by Cahill et al (2009). Likewise, some other studies also reported that advanced maternal age, parity, conception mode and chorionicity did not influence pregnancy loss after amniocentesis (Cahill et al, 2009;Chen et al, 2020;Daskalakis et al, 2009;Dechnunthapiphat et al, 2020;Lenis-Cordoba et al, 2013). To the authors' knowledge, there are no earlier reports on cervical length as a risk factor in twin pregnancies after amniocentesis.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Only abnormal ultrasound findings were associated with increased risk, similar to that reported by Cahill et al (2009). Likewise, some other studies also reported that advanced maternal age, parity, conception mode and chorionicity did not influence pregnancy loss after amniocentesis (Cahill et al, 2009;Chen et al, 2020;Daskalakis et al, 2009;Dechnunthapiphat et al, 2020;Lenis-Cordoba et al, 2013). To the authors' knowledge, there are no earlier reports on cervical length as a risk factor in twin pregnancies after amniocentesis.…”
Section: Discussionsupporting
confidence: 80%
“…A more recent study of twin pregnancies not in the meta-analysis included 332 twin pregnancies undergoing amniocentesis, and the pregnancy loss rate before 24 weeks was 3.0% (Dechnunthapiphat et al, 2020). Chen et al (2020) reported that the pregnancy loss rate before 28 weeks in 418 twin pregnancies was 1.91%. The pregnancy loss rate only related to the procedure in our study was the lowest among all the studies, mainly due to sticking to the standard protocol that helped exclude potential infection and cervical incompetence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive prenatal diagnosis is recommended when the NIPT result indicates a high risk of abnormalities or when ultrasound suggests a foetal structural malformation. Amniocentesis in twin pregnancies carries a slightly higher risk of foetal loss than in singleton pregnancies [ 9 ], and many twin pregnancies are conceived through artificially assisted reproduction or at an advanced age; therefore, it is a common phenomenon for twin-pregnant women to refuse prenatal diagnosis after a long period of hesitation.…”
Section: Introductionmentioning
confidence: 99%
“…In this study 3 , the primary outcome was the rate of fetal loss at any stage during pregnancy following CVS or first-trimester scan. Instead, miscarriage, defined as fetal loss before 24 weeks' gestation, might be more suitable for assessing the risk of CVS, as fetal death late in gestation is more likely to be due to other causes related to twin pregnancy itself [4][5][6] . It would be interesting to know whether the same conclusions could be drawn if the primary outcome measure were restricted to miscarriage.…”
mentioning
confidence: 99%